UPAYA SATLANTAS POLRES KUTAI TIMUR DALAM MENERTIBKAN PELANGGARAN LALU LINTAS DI WILAYAH HUKUM POLRES KUTAI TIMUR - DIMAS DWI NUR ROHIM (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            Transportation is a very important and strategic means in smoothing the economy, and other activities with the aim of strengthening unity and integrity and influencing aspects of national and state life. Increasing population and growing economy of the economy in developing countries such as Indonesia requires people to have high mobility in order to meet their daily needs.            Guidance on the attitudes and compliance of motor vehicle drivers regarding traffic regulations has been carried out by the East Kutai Police Traffic Unit, but with an imbalance between the number of motorized vehicle ownership and access not increasing this road, it has resulted in various types of traffic violations. which is difficult to minimize.            Driving by car or motorcycle on a big road that has super busy traffic traffic is certainly not an easy and comfortable thing. In addition to being troubled by traffic jams, we are often treated to some "iron horse" rider actions that still have a low level of safety awareness driving. This effect, in addition to increasing the number of traffic accidents, will also create a domino effect that is increasingly regarded as a daily traffic habit. Even not infrequently, making us uncomfortable in driving.            Based on this background, questions can be formulated in the form of the following questions: (1) What are the Factors that Caused Traffic Violations in the East Kutai District Police Legal Area? (2) How is the Satlantas effort in minimizing traffic violations in the East Kutai District Police Legal Area?            So it can be concluded (1) One of the factors causing traffic violations in the area of East Kutai is human factors. Related types of violations are vehicle registration, standard helmets, speed, and many more. Law enforcement given by law enforcement officers is to provide preventative effects so that violations are not repeated, with hopes that the fines given to violators make them aware of not repeating the same violations. (2) There have been a number of efforts made by the East Kutai Regional Police Headquarters to reduce the number of traffic violations, namely the implementation of Law No. 22/2009 concerning Traffic and Road Transportation. Keywords: Control, Traffic, Violation